Legal Protection for Investors in Bitcoin Transactions on Exchange Platforms - Siregar, Dahris (Fakultas Hukum, Universitas Krisnadwipayana, 2025)
Since the introduction of Bitcoin, the first cryptocurrency, virtual currencies have become a topic of increasing public concern. Bitcoin trading is highly speculative and involves significant risks, as its value can fluctuate dramatically over time, with no single party held accountable for these changes. This study focuses on the protection of investors engaged in Bitcoin transactions on exchange platforms in Indonesia under positive law. The research employs a normative juridical approach, with both primary and secondary data sourced from legal texts, regulations, and relevant literature. The findings indicate that Bitcoin transactions in Indonesia primarily involve the sale of commodity assets through exchange platforms, which function as physical traders of crypto assets. Regulatory frameworks established by futures regulatory bodies play a crucial role in preventing fraud and safeguarding legal rights. According to Indonesian Contract Law, as outlined in the Civil Code (Burgerlijk Wetboek, BW), Bitcoin transactions are considered “legal” when they fulfill the contractual conditions specified in Article 1320. Consequently, investors are legally protected from both criminal and civil liabilities due to the validity of these transactions.